Laboratory course on fundamentals of nuclear physics study aid учебно-методическое пособие - Ryzhakova (Rizhakova) Physicist Associate Professor of Tomsk Polytechnic University, Candidate of physical and mathematical sciences; Rogova Physicist Associate Professor of Tomsk Polytechnic University, Candidate of Technical Sciences; Verkhoturova linguist Head of the Department of Tomsk Polytechnic University, Candidate of historical sciences; Cherepennikov physicist Associate Professor of Tomsk Polytechnic University, Candidate of Sciences (TPU Publishing House, 2022)
The study guide presents 8 laboratory works on the course "Fundamentals of Nuclear Physics". The main attention is paid to issues of wide applied significance -radioactivity, interaction of radiation with matter, and nuclear physics methods of analysis. The principles and methods of a- and y-spectrometry and fundamentals of neutron activation analysis are considered.. The guide is intended for students studying in the directions 14.03.02, 14.04.02 '"Nuclear physics and technologies". 14.05.02 "Nuclear power plants: design, operation and engineering". 14.05.04 "Electronics and automation of physics installations".